Species Complexes of the Oribatid Mites (Sarcoptiformes, Oribatei) in Soils of Urban Street Lawns with Different Pollution Rates - Shevchenko, O.S.; Kolodochka, L.A. (Вестник зоологии, 2013)
Species complexes of oribatid mites at six plots on the street lawns in one of Kyiv districts are studied. In total 27 species of 26 genera and 19 families of oribatid mites are found. Direct correlation between oribatid species diversity and the level of total soil pollution is not shown.